Site predilection of extrapulmonary tuberculosis: study from a tertiary care centre - Mavila, Rajani; Kottarath, Manoj; Nair, Smitha; Thaha, Milan Malik (International Journal of Research in Medical Sciences, 2017)
Background: Extrapulmonary tuberculosis (EPTB) still constitutes an important clinical problem. We aimed to evaluate the site prevalence of extrapulmonary tuberculosis. Methods: We retrospectively evaluated 187 extrapulmonary tuberculosis patients diagnosed between 1st June 2013 and 31st May 2015 in a tertiary care hospital, Kanpur, Kerala, India. Results: Among the extra pulmonary tuberculosis 112 (59.9%) were males. About 170 (90.9%) patients received CAT1 treatment and 17 (9%) patients received CAT2 treatment. Overall, the total number of different types of EPTB cases included Lymph node (n=55, 29.41%), GIT (n=45, 24.04%), Pleura (n=44, 23.53%), Skeletal (n =14, 7.49%), CNS (n=7, 3.74%) EPTB cases other site included mainly genitourinary (6), breast (6), skin (5), pericardium (3), Psoas (4) a vocal cord (1) and eye (1). Conclusions: EPTB still constitutes an important clinical problem. In the current study, we assessed the site of predilection of EPTB patients. In this study, EPTB cases constituted 52.08% of all tuberculosis cases presented to our center in the study period. Lymph node tuberculosis is the most common type.